Linguistic transformations in the linguistic landscape of Nur-Sultan - Zharkynbekova, Ш.К.; Seitkhanova, А.Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
This article is devoted to the study of the linguistic landscape of the city. The results of a study are presented in January-March 2019 in the city of Nur Sultan are presented. Various definitions of the term “linguistic landscape” are considered, a circle of issues are outlined that require further scientific discussion is outlined. A sociolinguistic analysis was carried out from the point of view of compliance of the linguistic landscape of the city with the Law on the Languages of the Republic of Kazakhstan, a functional distribution was established of languages used on various city signs was established. The description of the linguistic landscape of the city makes it possible to see not only the current situation using languages, but also to outline the prospects for the development of the state and other languages